Overlooked Leadership Potential: The Preference for Leadership Potential in Job Candidates Who Are Men vs. Women - Player, Abigail; Randsley de Moura, Georgina; Leite, Ana C.; Abrams, Dominic; Tresh, Fatima (Frontiers in Psychology, 2019)
Two experiments tested the value people attach to the leadership potential and leadership performance of female and male candidates for leadership positions in an organizational hiring simulation. In both experiments, participants (Total N = 297) valued leadership potential more highly than leadership performance, but only for male candidates. By contrast, female candidates were preferred when they demonstrated leadership performance over leadership potential. The findings reveal an overlooked potential effect that exclusively benefits men and hinders women who pursue leadership positions that require leadership potential. Implications for the representation of women in leadership positions and directions for future research are discussed.